The body dysmorphic symptoms scale: tradução, adaptação cultural e validação - Ramos, Tatiana Dalpasquale [UNIFESP] (2016)
INTRODUCTION: Rhinoplasty is one of the most sought after aesthetic surgeries by individuals with body dysmorphic disorder (BDD), which is characterized by an excessive dissatisfaction with appearance that may affect patient satisfaction with the results of surgery. OBJECTIVE: To translate into Brazilian Portuguese, cross-culturally adapt and validate the Body Dysmorphic Symptoms Scale (BDSS). METHODS: Eighty patients of both genders seeking rhinoplasty were selected at the Nose Outpatient Clinic (Division of Plastic Surgery, Federal University of São Paulo) between February 2014 and March 2015. Thirty patients participated in the cross-cultural adaptation phase. The instrument was tested for reliability in 20 patients and for construct validity in 50 patients by correlating the BDSS with the Brazilian version of the Yale-Brown Obsessive Compulsive Scale Modified for Body Dysmorphic Disorder (BDD-YBOCS). RESULTS: Internal consistency was tested using Cronbach's alpha coefficient (?=0.805). The BDSS showed excellent interobserver (r=0.909; ICC=0.873; p<0.001) and intraobserver (r=0.956; ICC=0.939; p<0.001) reliability. There was a significant difference in BDSS scores between patients with and without BDD symptoms (p<0.001), and a strong correlation (r=0.841; p<0.001) between BDD-YBOCS and BDSS scores. The area under the receiver operating characteristic (ROC) curve was 0.981, indicating good accuracy to discriminate the presence of BDD symptoms. Forty-six percent of patients had BDD symptoms (BDSS) and 54% presented moderate to severe appearance-related obsessive- compulsive symptoms (BDD-YBOCS). CONCLUSION: The cross-culturally adapted Brazilian version of the BDSS is a reliable instrument with face, content, and construct validity; it was named Body Dysmorphic Symptoms Scale-UNIFESP/EPM (BDSS-UNIFESP/EPM).